KRITIK TEORI BELAJAR MENURUT PANDANGAN ISLAM - Sadiran Sadiran (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2011)
Islamic Education requires that a teacher in addition to having a deep and broad knowledge of science to be taught, but also must be able to convey that knowledge effectively and efficiently and have a noble character. About the need for a noble character of a teacher has long been a concern and a review of the scholars of Islam in the century classic. For example, Ibn Muqaffa say that good teachers are teachers who want to try to start by educating themselves, improve their behavior, straightening his thoughts, and keep the words he said before delivering it to others. While the Imam Al-Ghazali said that: a teacher who deliver science should be clean, do and act as guidance as, being affectionate towards his pupils and students should treat them like his own son, the teacher must always control, advise, give a message - a message of moral about science and the future of their students and do not let them proceed to a higher learning before they have mastered the previous lesson and have a noble character. Balance the development of science (reason) and morality (the heart of behavior) is something that should always be controlled by the teacher. That is the teacher who in addition to foster reasonable intelligence can grow his thoughts also a noble character. So the theory of education according to Islamic education is to be as guidance as, being affectionate towards his pupils and students should treat them like his own son, the teacher must always control, advise, give a message - a moral message about science and the future of their students and do not let them continue learning to a higher before they have mastered the previous lesson and have a noble character. Islamic education in various aspects based on the values of noble and godlike universal, then the strategic step for us Muslims should realize the theory of learning by implementing Islamic education in accordance with the nature and character. In contrast to the theory of learning that emerged from the thinkers of the western experts educators.Key Words: Theory of learning, Islamic perspective, Islamic learning.